2016 International Conference on the Domestic Use of Energy (DUE) 2016
DOI: 10.1109/due.2016.7466703
|View full text |Cite
|
Sign up to set email alerts
|

Energy use scenarios in an informal urban settlement in Johannesburg, South Africa

Abstract: This paper presents a survey from a sample of 52 households from three informal urban settlements in Tembisa, Johannesburg, namely Vusimuzi, Madela Kufa Section 1 and Madela Kufa Section 2. The survey covered energy needs for cooking, space heating, water heating and lighting. No information was requested on the age, gender, status in the household, income level of the respondents, or the number of persons in the household. Coal was the primary source of energy for cooking, water heating and space heating, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Thus, energy interventions in this region need to consider demand factors and should be less supply driven, as supply does not always lead to uptake. [73][74]…”
Section: Determinants Of Household Fuel Choicementioning
confidence: 99%
“…Thus, energy interventions in this region need to consider demand factors and should be less supply driven, as supply does not always lead to uptake. [73][74]…”
Section: Determinants Of Household Fuel Choicementioning
confidence: 99%
“…Domestic biomass and fossil fuel combustion for space heating and cooking is also widely practised, especially in informal settlements that are found around most towns and cities (e.g. Kimemia et al, 2010;Vakkari et al, 2013;Butt et al, 2016;Makonese et al, 2016).…”
mentioning
confidence: 99%
“…The common occupants in South African informal settlements are often unemployed individuals, or those who falls in the low income brackets. In the study conducted by [63,64], it was found that majority of the households live on an average income of R3500. Predominately, adult males and females reside in informal settlements, while there is only a small number of school-going children [65].…”
Section: Methodsmentioning
confidence: 99%